The Therapeutic Effect of Artemisinin and Its Derivatives in Kidney Disease - Xia, Ming; Liu, Di; Liu, Yu; Liu, Hong (Frontiers in Pharmacology, 2020)
Artemisinin (ARS) and its derivatives (ARSs) are recommended as the first-line antimalarial drugs for the treatment of malaria. Besides antimalarial function, its potent anti-inflammatory and immunoregulatory properties, as well as the ability to regulate oxidative stress have brought them to a prominent position. As researchers around the world are continually exploring the unknown biological activities of ARS derivatives, experimental studies have shown much progress in renal therapy. This review aims to give a brief overview of the current research on ARSs applications for kidney treatment with the evaluation of therapeutic properties and potential molecular mechanisms.